226k views
2 votes
Si la suma de las inversas de las raíces de la ecuación: x^2-mx+1=0, es igual a la inversa de la suma de las raíces ¿qué valor asume «m»?

User Monfresh
by
5.5k points

1 Answer

1 vote

Let
x_1, x_2 be the two roots. The claim is that


(1)/(x_1)+(1)/(x_2)=(1)/(x_1+x_2)

We can rewrite this expression as


(x_1+x_2)/(x_1x_2)=(1)/(x_1+x_2)

Now, recall that if the leading term is 1, then you can think of a quadratic equation as


x^2-sx+p=0

i.e. the linear coefficient is the opposite of the sum of the roots, and the constant term is the product of the roots. In other words, we have


x_1+x_2=m,\quad x_1x_2=1

Substitute these values in the equation above to have


(m)/(1)=(1)/(m)

Which leads to


m^2=1 \iff m=\pm 1

User Skirsch
by
4.5k points